Integrating Islamic and Humanistic Values into the Merdeka Curriculum: Implications and Recommendations - Danang Eko Saputro (FTIK Program Magister PAI Institut Agama Islam Tarbiyatut Tholabah, 2025)
Integrating Islamic values ​​and humanism becomes a strategic approach to create harmony between spiritual and humanistic dimensions in the Independent Curriculum concept. However, in practice there is a lot of incomplete understanding of the Merdeka curriculum concept so that the Islamic and humanist values ​​contained in it are displaced. This research aims to explore the integration of Islamic values ​​and humanism in the Independent Curriculum, its implications for the formation of students' character, as well as strategic recommendations for policy makers and educators. This research uses a literature approach with the LSR (Systematic Literature Review) method and data analysis of Miles and Hubberman's theory. The results of the research show that the process of integrating Islamic and Humanist values ​​in the Independent Curriculum is a strategic step and a philosophical and practical basis for building an education system in Indonesia. The implication of the integration of Islamic values ​​and humanism in the Independent Curriculum is the creation of a solid foundation for educating students. Recommended implementation strategies are an integrative curriculum development strategy, teacher training in humanistic learning theory, implementation of a project to strengthen the Pancasila Student profile based on Islamic values, implementation of a holistic approach to early childhood education. Collaboration between schools, families and communities, as well as ongoing evaluation. This research provides a significant contribution as a basis for policy makers and educators to take strategic steps that are relevant to the demands of the times and the needs of students.